+0  
 
+1
487
1
avatar+1439 

Thanks so much!

 Dec 20, 2017

Best Answer 

 #1
avatar+8866 
+2

17  ≥  7    so    f(17)   =   17 - 13   =   4

 

4  <  7    so    f(4)   =   42 - 4   =   12

 

12  ≥  7    so    f(12)   =   12 - 13   =   -1

 

f(  f( f(17) )  )   =   f(  f( 4 )  )   =   f(  12  )   =   -1

 Dec 20, 2017
 #1
avatar+8866 
+2
Best Answer

17  ≥  7    so    f(17)   =   17 - 13   =   4

 

4  <  7    so    f(4)   =   42 - 4   =   12

 

12  ≥  7    so    f(12)   =   12 - 13   =   -1

 

f(  f( f(17) )  )   =   f(  f( 4 )  )   =   f(  12  )   =   -1

hectictar Dec 20, 2017

5 Online Users